STRUKTUR KOMUNITAS DAN KARAKTERISTIK MORFOLOGI UDANG AIR TAWAR DI PERAIRAN KAWASAN PULAU PEDALAMAN KABUPATEN MEMPAWAH - Sirojul, Achmad Mulyadi (Department of Aquatic Resource Management, Faculty of Agriculture, Universitas Tanjungpura, 2023)
Pulau Pedalaman is one of the villages in Mempawah Regency. This village has unique regional characteristics where this area is surrounded by flowing rivers that divide one land from another. The aim of this research is to determine the various types and characteristics of freshwater shrimp in Pulau Pedalaman waters, Mempawah Timur. This research was conducted from September to December 2021 at 5 observation stations. Based on the results, 8 species of shrimp were obtained which belonged to the genus Macrobrachium and Penaeidae. The morphological characteristics of shrimp in the waters of Pulau Pedalaman are Macrobrachium rosenbergii which has a dark black and patterned body color, with a total length of 8.3 cm, and a number of 13-14 rostrum teeth; Macrobrachium sp. has a black body color and black spots on the body, with a total length of 3-7 cm, and the number of rostrum teeth is 8; Macrobrachium sintangense has a reddish body color with a total length of 5-7 cm, and the number of rostrum teeth is 7-13; Macrobrachium equidens has a slightly black, patternless body, with a total length of 10.5-11.5 cm and a total of 9-10 rostrum teeth; Penaeus indicus has a white body and brown spots, with a total length of 2-12 cm, and the number of rostrum teeth is 7; Penaeus merguiensis has a white body color with brown spots, with a total length of 11 cm and a number of 2-8 rostrum teeth; Penaeus semisulcatus has a dark green body color with red or brown transverse lines, with a total length of 2-10 cm, and the number of rostrum teeth is 7-8; Litopenaeus vannamei has a spotted white body color, with a total length of 23 cm, and the number of rostrum teeth is 8-9. The physical and chemical parameters of the waters in the Pulau Pedalaman river meet fisheries quality standards for the growth and life of shrimp and fish.